Implementasi Manajemen Multikultural dalam Pencegahan Bullying di Madrasah Ibtidaiyah - Wati, Yulika; Hikmawati, Hanifah; Muttaqin, Muttaqin (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2025)
Multicultural education management in Islamic boarding schools is considered crucial as a response to the increasing number of bullying cases caused by a lack of understanding of cultural, ethnic, and social differences. This study aims to analyze the implementation of multicultural education management in preventing bullying at Madrasah Ibtidaiyah Madinatul Huffadz Ngawi. This study used qualitative methods with data collection techniques in the form of observation, interviews, and documentation, and analyzed using open coding through NVivo 12 Plus software. The results showed that bullying prevention strategies were implemented through programmatic and non-programmatic approaches such as moral studies, weekly deliberations, mutual cooperation, foster parent programs, and anti-bullying seminars. The results showed that this management created a tolerant and inclusive learning climate. In conclusion, multicultural strategies have proven effective in reducing bullying. The practical contribution of this study is to provide a concrete model for Islamic boarding school managers or similar educational institutions in implementing multicultural education management strategies to prevent bullying. Existing programs have been proven to form healthy social interactions and raise awareness of the importance of tolerance.